A singular remedy: cinchona across the atlantic world, 1751-1820 - Gänger, Stefanie (University of Cambridge ESOL Examinations, 2020)
Innovative exploration of how medical knowledge was shared between and across diverse societies tied to the Atlantic World around 1800.
Description based on publisher supplied metadata and other sources
Keywords: Geschichte 1751-1820; Pharmazie; Chinarindenbaum